Geleneğin müdafaası: Mahmûd Muhammed Şâkir’in Esrârü’l-Belâga’ya yazdığı ön söz (inceleme-tercüme-notlandırma) - ARAZ, İSMAİL (My University, 2023)
XX. yüzyılda İslam âleminde gerçekleştirilen ıslahatlar zamanla siyasi ve askerî boyutları geride bırakarak dinî ve sosyokültürel alanları kapsayacak şekilde genişlemiştir. Müsteşriklerin önemli uğrak yerlerinden biri olan Mısır’da sürdürülen eğitim sistemi de bu ıslahat hareketlerinden nasibini almıştır. Özellikle Ezher’de takip edilen müfredatın gözden geçirilerek yenilenmesi, ıslahatı hayatın her alanına yaymak isteyenlerin hedefi olmuştur. Bunların başında gelen Muhammed Abduh’a göre yeni ve özgün bir ilim anlayışı için Ezher’de okutulan bazı eserlerin yenilenmesi kaçınılmazdı. Abduh, yenilik çağrısı yapmakla yetinmemiş; aynı zamanda Ezher’de okutulan belâgat eserlerini hedef alarak belâgat geleneğinde iz bırakan âlimleri tahkir edecek kadar ileriye gitmiştir. O, Ezher uleması ile girdiği fikri çatışma sürecinde Sekkâkî, Kazvînî ve Teftâzânî gibi müteahhir dönem belâgat âlimlerini küçümseyici ifadelerle tenkit etmiştir. Bu durum yeni yetişen talebeler arasında geleneğe karşı küçümseyici bir algının oluşmasına yol açmıştır. Söz konusu algının menfi etkilerine tanık olan Mahmûd Muhammed Şâkir, geleneği tahkir eden ve âlimleri yıpratan böyle bir anlayışa karşı çıkmıştır. Yazılarında İslam medeniyetinin ilmî birikim ve zenginliğine vurgu yaparak geleneği müdafaa eden Şâkir, tahkik ettiği Esrârü’l-belâga isimli eserin ön sözünde Abduh ve onun söylemlerinin izinden giden Reşîd Rızâ, Berkûkî ve Tâhâ Hüseyin’in veba olarak tarif ettiği görüşlerine yer vererek sebep oldukları yozlaşmaya değinmiştir. Buradan hareketle çalışmada Şâkir’in söz konusu görüşleri ele alınmıştır. Konunun kapsamlı bir şekilde anlaşılabilmesi için öncelikle Şâkir’i geleneği savunmaya sevk eden sebepler üzerinde durulmuştur. Ardından Abduh ve onun izinden giden isimlere yönelttiği tenkitlerin iç yüzüne ulaşılmaya çalışılmıştır. Şâkir’in Abduh’u tenkit etmesine yol açan faktörlerin araştırmacılar tarafından daha iyi anlaşılabilmesi amacıyla çalışmada tarihî verilere bağlı kalınarak endüksiyon (tümevarım) yöntemi benimsenmiştir. Son kısımda ise Şâkir’in geleneği müdafaa ettiği ön sözün tercümesine yer verilmiştir. Bu çalışmanın temel vurgusu, belâgat ilminde otorite âlimlerin ilmî kimliklerini serimlemede önemli işleve sahip olan derinlikli okumanın zaruretini ortaya koymaktır.

The reforms carried out in the Islamic world in the 20th century with time have expanded to include religious and socio-cultural fields, leaving behind the political and military dimensions. The education system maintained in Egypt, which was one of the important haunts of the orientalists, also got its share from these reformist movements. In particular, the revision and renewed in the curriculums followed in Azhar by reviewing them has been goal of those who want to spread reform in all areas of life. According to one of these people, Muhammad Abduh, it was inevitable to renew some of the works taught in Azhar for a new and original understanding of science. Abduh not only called for innovation; but at the same time by targeting the rhetoric works taught in Azhar, he took the issue to such a level that he insulted the scholars who left their mark on the tradition of rhetoric. During the intellectual conflict with the Azhar scholars, he criticized the rhetoric scholars of the late period such as al-Sakkākī, al-Ḳazwīnī and al-Taftāzānī with condescending expressions. This situation led to the formation of a contemptuous perception towards tradition among newly trained students. Mahmud Muhammad Shākir, who witnessed the negative effects of this mentioned perception, opposed such an understanding that insulted tradition and tried to wear down competent scholars. Shākir, who defended the tradition by emphasizing the scientific accumulation and richness of Islamic civilization in his writings, gave a wide place to the destruction caused by Abduh and his followers in the preface of the work called Asrār albalāgha. In his foreword, Shākir also mentioned the views of Abduh and who continued his discourses such as Rashīd Rıḍā, al-Barqūqī and Ṭāhā Ḥusayn, and referred to corruption caused by the views he described as the plague. From this point of view, in this study, Shākir's views are discussed. For a better understanding of the subject, first, the reasons that made Shākir an advocate of tradition were emphasized. In this way, it has been tried to reach the inner circle of the criticisms directed to Abduh and his followers. In order for the researchers to better understand the factors that caused Shākir to criticize Abduh, the induction method was adopted by adhering to the historical data in the study. At the end of the study, the translation of the preface in which Shākir defends the tradition is given. The main emphasis of this study, which was prepared to understand the scholars who made their influence in the tradition of rhetoric permanent, in a way that reflects the richness of Islamic civilization, is the necessity of in-depth reading that reveals the scientific identities of the scholars.
Keywords: Arabic Language and Rhetoric; al-Talkhīṣ; al-Taftāzānī; Muhammad Abduh; Ras̲h̲īd Riḍā; ʻAbd al-Raḥmān al-Barqūqī; Ṭāhā Ḥusayn; Mahmūd Muhammad Shākir; Tradition.; Arap Dili ve Belâgati; Telhîs; Teftâzânî; Muhammed Abduh; Reşîd Rızâ; Abdurrahman el-Berkûkî; Tâhâ Hüseyin; Mahmûd Muhammed Şâkir; Gelenek.